Methodology of Forming Professional Skills in Students Based on an Integrative Approach - Khaliljanovna, Makhmudova Feruza; Muhabbat, Hakimova (ASEAN Journal of Educational Research and Technology, 2024)
This article explores the challenge of equipping master's students in software engineering with the skills necessary for professional communication. It examines the job functions of programmers and the competencies outlined in the Federal State Educational Standards, highlighting a gap in readiness for professional communication. The research aims to develop a model to enhance this readiness in future master's students. The study involves creating and testing a model-building algorithm, analyzing relevant documents, refining the concept of communication readiness, and constructing a structural educational model. The methodology incorporates systemic, competency-based, and integrative approaches, using various analytical and modeling methods. The findings reveal a lack of sufficient readiness for professional communication among software engineering students. To address this, the authors propose an interdisciplinary model within the university curriculum, focusing on interactive teaching methods, interdisciplinary projects, and modern educational internet resources to boost student motivation and engagement. This model holds potential for application in master's level training programs, offering a framework to develop competencies in various aspects of professional communication, including business, scientific, and intercultural communication skills.